Effects of Abdominal Massage to Overcome Gastrointestinal Dysfunction in Patients in Intensive Care Unit: A Literature Review - Cecep Eli Kosasih; Alisha Dewi Andriani; Astriani Ayu Lestari; Friska Maulia Sekarjati; Hanifa Iqomatulhaq; Janet Jessica Audini; Mia Vauziah Lestary; Mohamad Ramdan; Renie Nurcholivatun; Risna Risela Agustin; Tanti Almuwaroh; Yoga Abdul Manaf; Titin Mulyati (Universitas Padjadjaran, 2019)
Patients who are receiving treatment at the ICU have at least one symptom of gastrointestinal dysfunction including decreased bowel noise, abdominal distension, constipation, decreased frequency of defecation, and increased GRV (gastric residual volume). Non-pharmacological interventions that can be done to improve gastrointestinal function include abdominal massage. This paper aimed to conduct a literature review on the effects of abdominal massage to overcome gastrointestinal dysfunction in patients in the ICU. Articles taken from the Google Scholar and Science Direct electronic databases with the keywords abdominal massage, gastrointestinal function, bowel function, and ICU were published from 2015 to 2019. There were four research articles discussing abdominal massage to improve gastrointestinal function. Three articles used the Randomized Controlled Design method and one article used the Quasi Experimental method. Abdominal massage has a positive effect to improve gastrointestinal function in patients receiving treatment in the ICU. Improved gastrointestinal function that can be seen from the existence of a faster time in the reduction in gastric residual volume (GRV), decreased abdominal circumference, decreased gastric distension, and decreased the incidence of constipation. It is expected that abdominal massage can be applied by ICU nurses considering this intervention has the effectiveness in terms of time and funding.Keywords: Abdominal Massage, Gastrointestinal Function, Intensive Care Unit